Multiwavelength Properties of Infrared-faint Radio Sources Based on Analysis of Their Spectral Energy Distribution - Yihang Zhang; Lulu Fan; Tao An; Jun Yang; Weibin Sun; Haoran Yu; Yunkun Han (The Astrophysical Journal)
Infrared-faint radio sources (IFRSs) are believed to be a rare class of radio-loud active galactic nuclei (AGNs) characterized by their high radio-to-infrared flux density ratios of up to several thousand. Previous studies have shown that a fraction of IFRSs are likely to be hosted in dust-obscured galaxies. In this paper, our aim is to probe the dust properties, star formation rate (SFR), and AGN activity of IFRSs by modeling the UV-to-infrared spectral energy distribution (SED) of 20 IFRSs with spectroscopic redshifts ranging from 1.2 to 3.7. We compare the Bayesian evidence of a three-component model (stellar, AGN, and cold dust) with that of a two-component model (stellar and cold dust) for six IFRSs in our sample with far-infrared photometry and find that the three-component model has significantly higher Bayesian evidence, suggesting that IFRSs are most likely to be AGNs. The median SED of our IFRS sample shows similarities to an AGN–starburst composite in the IR regime. The derived IR luminosities of IFRSs indicate that they are low-luminosity counterparts of high-redshift radio galaxies. We disentangle the contributions of AGN-heated and star formation-heated dust to the IR luminosity of IFRSs and find that our sample is likely AGN-dominated. However, despite the evidence for significant impact of an AGN on the host galaxy, the AGN luminosity of our sample does not show correlation with the SFR of the sources.